1996
DOI: 10.1007/bf01084367
|View full text |Cite
|
Sign up to set email alerts
|

Scintimammography with technetium-99m tetrofosmin in the diagnosis of breast cancer and lymph node metastases

Abstract: The aim of the study was to evaluate the possible role of scintimammography (SMM) with technetium-99m tetrofosmin in breast cancer. Thirty-three patients with breast disease and ten normal controls were included in the study. Planar scintigraphic images in supine anterior, prone lateral and lateral views, with the patient lying in lateral recumbency, were acquired. A qualitative analysis evaluating both breasts and lymph nodes was performed. All breast lesions were verified after surgery and/or by fine-needle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…Therefore, there is growing interest in the scintigraphic evaluation of suspicious axillary lymph node involvement, similar to that in the use of scintimammography for primary breast cancer detection. Our results showed that on early scans, 99m Tc-MIBI imaging correctly identified 12 of 22 patients with axillary lymph node involvement, which is similar to findings reported elsewhere [16,19,28,34]; the rate of identification on delayed scans was slightly lower. Negative results using 99m Tc-MIBI included all of the lymph nodes missed on scintimammography which were less than 10 mm in size.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, there is growing interest in the scintigraphic evaluation of suspicious axillary lymph node involvement, similar to that in the use of scintimammography for primary breast cancer detection. Our results showed that on early scans, 99m Tc-MIBI imaging correctly identified 12 of 22 patients with axillary lymph node involvement, which is similar to findings reported elsewhere [16,19,28,34]; the rate of identification on delayed scans was slightly lower. Negative results using 99m Tc-MIBI included all of the lymph nodes missed on scintimammography which were less than 10 mm in size.…”
Section: Discussionsupporting
confidence: 94%
“…There is growing interest in the scintigraphic evaluation of suspicious breast masses. Radiopharmaceuticals including fluorine-18 fluorodeoxyglucose (FDG), thallium-201, technetium-99m hexakis 2-methoxyisobutylisonitrile (MIBI), 99m Tc-tetrofosmin and 99m Tc complexes of diphosphonates such as methylene diphosphonate (MDP) and hydroxymethylene diphosphonate (HMDP) have been investigated as complements to diagnostic imaging procedures in patients with suspected breast cancer [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. FDG positron emission tomography (PET) has been suggested as a reliable technique for breast cancer detection, but its use is restricted by the high cost and by manpower considerations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our results, Taillefer et al [25] reported 79.2% sensitivity and 84.6% specificity in the diagnosis of axillary lymph node involvement of 99m Tc-MIBI in a study of 100 patients and Danielsson et al [26] reported 67% sensitivity and 80% specificity for 99m Tc-MIBI planar images in 58 patients. Using 99m Tc-tetrofosmin, other researchers reported 57, 72 and 91.6% sensitivity and 100% specificity in the diagnosis of axillary lymph node metastasis [20][21]27]. The low sensitivity in the detection of axillary lymph node metastasis may be due to a patient's characteristics or the patient's position during image acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant portion of cancers are missed; furthermore, equivocal findings require followup studies by biopsy or by another imaging study. Scintimammography has generated much interest as an adjunct to x-ray mammography both for detecting a tumor not shown on the the x-ray techniques [1] and for identifying its type and assessing the prognostic threat that it poses [2,3]. Scintimammography is of interest also for particular patient populations, e.g., women with dense breasts (for whom mammography may be less Manuscript effective), for cases of indeterminate mammograms [4,5] and high-risk patients (e.g., prior cancer, strong family history, lobular cancer in situ) [6].…”
Section: Introductionmentioning
confidence: 99%